Pengaruh Kepercayaan Diri dan Motivasi Terhadap Performance Pertandingan Atlit Karate di Forki Lampung - Hendri Dunan; Ayu Sulistiandari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study investigates the effect of self-confidence and motivation on the performance of karate athletes in ForKI Lampung. Qualitative descriptive methods are used to describe the problems faced by athletes during matches, especially doubts and defeats against opponents who are below their abilities. The success of athletes in achieving high achievements does not only depend on physical abilities but is also influenced by psychological factors. The results of the study show that self-confidence and motivation play a key role in determining match performance. Athletes with high levels of self-confidence and strong motivation tend to perform better. However, to achieve maximum results, athletes need to have the determination to become champions and get support that strengthens their motivation during the game. This research provides a deeper understanding of the problems faced by karate athletes in ForKI Lampung and highlights the importance of self-confidence and motivation in improving performance. The results of this study can be used as a basis for developing strategies and interventions that are effective in building athlete's confidence and motivation. Thus, it is hoped that athletes can achieve optimal results in the competition.